2022
DOI: 10.1177/00332941221121564
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Market Culture, Clan Culture, Benevolent Leadership, Work Engagement, and Job Performance: Leader’s Dark Triad as a Moderator

Abstract: Benevolent leadership is one of the leadership styles which provides a positive influence on employees. However, the current leadership literature has yet to investigate how benevolent leadership leads to job performance, the processes involved, the relationship between organizational culture and benevolent leadership, and the role of dark side of leaders in affecting this relationship. Using the leader-culture fit framework within an Eastern context, the current study first investigates the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
0
1
0
3
Order By: Relevance
“…The results showed that authoritarian leadership damaged employees’ work engagement since it was taken as a hindrance job demand, 16 , 77 and benevolent leadership may either improve work engagement when considered as a job resource, 77 or impair employees’ work engagement since its nature of showing consideration may signal that one could get rid of penalties and reap profits even if they loaf on the job. 78 However, the impact of authoritarian-benevolent leadership style on followers is less clear. 20 This study focused on the unique feature of inconsistency possessed by authoritarian-benevolent leadership style and analyzed this effect based on social information processing theory, which provides a new theoretical basis for future research to explore the impacts of ambidextrous leadership.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that authoritarian leadership damaged employees’ work engagement since it was taken as a hindrance job demand, 16 , 77 and benevolent leadership may either improve work engagement when considered as a job resource, 77 or impair employees’ work engagement since its nature of showing consideration may signal that one could get rid of penalties and reap profits even if they loaf on the job. 78 However, the impact of authoritarian-benevolent leadership style on followers is less clear. 20 This study focused on the unique feature of inconsistency possessed by authoritarian-benevolent leadership style and analyzed this effect based on social information processing theory, which provides a new theoretical basis for future research to explore the impacts of ambidextrous leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, benevolent leaders recognize the significance of work-life balance and employee well-being, emphasizing the need for a harmonious equilibrium between work and personal life. By prioritizing wellbeing, they alleviate stress, cultivate job satisfaction, and encourage a positive integration of work and personal life, thereby enhancing job engagement [25,51,52]. In conclusion, the connection between benevolent leadership and job engagement is a reciprocal one.…”
Section: Relationship Between Benevolent Leadership and Job Engagementmentioning
confidence: 97%
“…Plett (2019) lebih lanjut mengatakan bahwa penelitian mengenai hubungan tipe budaya organisasi Cameron & Quinn (2011) dan keterlibatan kerja masih terbatas, sehingga ini merupakan sebuah ruang penelitian yang dapat dilakukan untuk memperkaya pengetahuan mengenai hubungan kedua variabel tersebut. Kehadiran mediator banyak digunakan untuk untuk melihat hubungan tidak langsung antara kedua variabel tersebut dan terbukti bahwa kehadiran mediator dapat memperbesar effect size dari budaya klan terhadap keterlibatan kerja karyawan (Lee & Ding, 2022;Reis dkk., 2016). Maka dari itu, penelitian ini juga akan menggunakan mediator untuk melihat hubungan tidak langsung antara kedua variabel tersebut.…”
Section: Pendahuluanunclassified
“…Budaya klan secara tidak langsung dapat mempengaruhi keterlibatan kerja dan kinerja karyawan (Lee & Ding, 2022). Penelitian sebelumnya telah menemukan bahwa terdapat hubungan yang positif antara budaya klan dengan keterlibatan kerja (Plett, 2019) dan juga adanya hubungan positif antara kepemimpinan dan keterlibatan kerja (Rahmadani & Schaufeli, 2020).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation